Solution of direct and inverse conduction heat transfer problems using the method of fundamental solutions and differential evolution. Issue 9 (3rd June 2020) - Basílio, Adam; Lobato, Fran Sérgio; Arouca, Fábio de Oliveira
Abstract : Purpose: The study of heat transfer mechanisms is an area of great interest because of various applications that can be developed. Mathematically, these phenomena are usually represented by partial differential equations associated with initial and boundary conditions. In general, the resolution of these problems requires using numerical techniques through discretization of boundary and internal points of the domain considered, implying a high computational cost. As an alternative to reducing computational costs, various approaches based on meshless (or meshfree) methods have been evaluated in the literature. In this contribution, the purpose of this paper is to formulate and solve direct and inverse problems applied to Laplace's equation (steady state and bi-dimensional) considering different geometries and regularization techniques. For this purpose, the method of fundamental solutions is associated to Tikhonov regularization or the singular value decomposition method for solving the direct problem and the differential Evolution algorithm is considered as an optimization tool for solving the inverse problem. From the obtained results, it was observed that using a regularization technique is very important for obtaining a reliable solution. Concerning the inverse problem, it was concluded that the results obtained by the proposed methodology were considered satisfactory, as even with different levels of noise, good estimates for design variables in proposed inverse problems were obtained. Design/methodology/approach: In this contribution, the method of fundamental solution is used to solve inverse problems considering the Laplace equation. Findings: In general, the proposed methodology was able to solve inverse problems considering different geometries. Originality/value: The association between the differential evolution algorithm and the method of fundamental solutions is the major contribution.